1. Usuń nawiasy i wykonaj redukcję wyrazów podobnych:
A) (6a2 + 2a + 1) - (-3a2 - 2a + 5)
B) - (2x2 + 4x – 3) + (-x2 -2x + 4)
C) 5x + (2x - 7) - 9x - (-3x + 8) + 20 - 8x
D) 7x - 3(5x - 2) - 6(-7 + 2x)
E )-5(3y - 7) + 2(6 - 4y) + 3y

2. Oblicz wartość liczbową wyrażenia:

A) –3xy3 + 3xy dla x = -1 , y = 2


B) 9y – (7y + x) + (6x – 7y) dla x = -2 , y = -3


Odpowiedź :

Odpowiedź:

1.

A) 6a2+2a+1+3a2+2a-5=9a2+4a-4

B) -2x2-4x+3-x2-2x+4=-3x2-6x+7

C) 5x+2x-7-9x+3x-8+20-8x=-7x+5

D) 7x-15x+6+42-12x=-20x+48

E) -15y+35+12-8y+3y=-20y+47

2.

A) -3*(-1)*2³+3*(-1)*2=24-6=18

B) 9*(-3)-(7*(-3)+(-2))+(6*(-2)-7*(-3))=-27+23+9=5